Noopolitics and Information Network Systems - Nikonov, Sergey Borisovich; Baichik, Anna Vitalievna; Zaprudina, Rikka Victorovna; Labush, Nikolai Sergeevich; Smolyarova, Anna Sergeevna (International Review of Management and Marketing, 2015)
This article discusses the measures that the states can use to prevent information expansion. The modern world is an information field, where information battles are conducted for the right to manipulate the electorate. Technical abilities to collect and analyze the obtained information differ across the countries. There is a struggle for leadership in this area. The article involves one of the most important aspects of application of noopolitics – confidence. Symbiosis of politics and psychology is one of the requirements to be considered by an international actor in the development of an information strategy. Keywords: Noopolitics, mass media, confidence, journalism, information system. JEL Classifications: D83; F52; F53; F55; O31; O32; O33